Go-Jek Motor Driver's Patience and Work Commitment - Siti Qodariah; Tanti Amalia Fikriana; Andy Putera; Savitri Yasmin (Psikologia : Jurnal Psikologi, 2018)
The online-based transportation is very helpful for people in doing activities. Besides being easy to reach, online transportation also offers cheap and fast prices. One company that develops online transportation is Go-Jek. The presence of Go-jek is a negative thing for conventional transportation services., Conventional transportation drivers conduct large-scale demonstrations until anarchic action against Go-Jek drivers. Although there are problems on the road, Go-Jek drivers committed to the company in carrying out their duties. With these problems, Go-Jek drivers are required to be patient, they persevere to keep working. This is interesting to study. Therefore this research is important to do, because it aims to see how patience and work commitment of Go-Jek drivers. The sample of research subjects was 95 people. The results of this study indicate that most Go-Jek motorcycle drivers have a low level of patience and work commitment